TiO2 BEADS FOR PHOTOCATALYTIC DEGRADATION OF HUMIC ACID IN PEAT WATER - Winarti Andayani; Agustin N M Bagyo (Universitas Gadjah Mada, 2011)
Degradation of humic acid in aqueous solution containing TiO2 coated on ceramics beads under irradiation of 254 nm UV light has been conducted in batch reactor. The aim of this experiment was to study photocatalytic degradation of humic acid in peat water. The irradiation of the humic acid in aqueous solution was conducted in various conditions i.e solely uv, in the presence of TiO2-slurry and TiO2 beads. The color intensity, humic acid residue, conductivity and COD (chemical oxygen demand) of the solution were analyzed before and after irradiation. The compounds produced during photodegradation were identified using HPLC. The results showed that after photocatalytic degradation, the color intensity and the COD value of the solution decreased, while the conductivity of water increased indicating mineralization of the peat water occurred. In addition, oxalic acid as the product of degradation was observed.